Trends of Transfusion Transmissible Infections Among Blood Donors by Chemiluminescent Assay in a Tertiary Care Centre - Krupal, V Sandhya; Renuka, I V; Ramya, Chitturi; Vaishnavi, R (Annals of Pathology and Laboratory Medicine, 2020)
Background: Blood transfusion is an important, integral and life saving procedure but simultaneously, carries risk of transmitting Transfusion Transmissible Infections(TTIs). The present study was done to find out the seroprevalence and changing trends of various TTIs among blood donors. Methods: Blood donors who attended our blood bank during May 2014 to May 2019 and fulfilled uniform guidelines approved by National blood transfusion council were included. Data regarding type of donors, sex and screening test results were collected from the records. Result: Out of 32046 donors, voluntary donors(76.3%) were more in comparison to replacement donors(23.7%) and out of 32046, 31944(99.7%) were males and 102(0.3%) were females. Amongst TTIs, seroprevalence of HBV(1.3%) was highest in the blood donors followed by HCV(0.65%),HIV (0.29%),Syphilis (0.06%) and Malaria(0.006%). TTIs were more seroprevalent in replacement donors than voluntary donors. Conclusion: TTIs were more in replacement donors than voluntary donors. A decreasing trend in the seropositivity percentage of most of the TTIs was seen due to strict donor selection criteria and counselling of blood donors. Stringent screening, implementation of more sensitive tests like Nucleic acid amplification test/Chemiluminescent assay and public awareness programs are needed to improve the prevention of TTIs.